Jemuran Pintar Dengan Sensor Ldr, Sensor Hujan, Sensor Suhu Dan Sensor KecepatanAngin Berbasis Arduino - Banjarnahor, Togap Munaz; Sumarno, Sumarno; Damanik, Bahrudi Efendi; Gunawan, Indra; Kirana, Ika Okta (Forum Kerjasama Pendidikan Tinggi, 2019)
Rapid technological advances that this time we can use to protect our clothesline out of the rain or the weather is not friendly. By using Arduino Mega2560 as the control center, we can design a system prototype for smart clothesline. In this research, the design proposes a clothesline smart equipped with a light sensor, rain sensor, humidity sensor, wind speed sensor, and equipped with fans and lights as the clothes dryer in wet or damp conditions. We do not need to worry about the clothes that are on the line if the weather conditions are not friendly or clothes are still wet or damp, because it is protected with a clever system whereby clothesline clothesline will be entered into a security room at a time when the weather in the rain, overcast, or strong winds and when clothes are safety dirungan still wet or damp, eating humidity sensor will give input to the Arduino Mega 2560 to carry out the drying process by the fan and lights so we do not have to worry anymore if the clothes are dried in the sun is still wet or damp. The design tool created smart clothesline as a whole can work well and allow can be applied in everyday life.